GraphoGame – a catalyst for multi-level promotion of literacy in diverse contexts - Ojanen, Emma; Ronimus, Miia; Ahonen, Timo; Chansa-Kabali, Tamara; February, Pamela; Jere-Folotiya, Jacqueline; Kauppinen, Karri-Pekka; Ketonen, Ritva; Ngorosho, Damaris; Pitkänen, Mikko; Puhakka, Suzanne; Sampa, Francis; et al. (Frontiers in Psychology, 2015)
GraphoGame (GG) is originally a technology-based intervention method for supporting children with reading difficulties. It is now known that children who face problems in reading acquisition have difficulties in learning to differentiate and manipulate speech sounds and consequently, in connecting these sounds to corresponding letters. GG was developed to provide intensive training in matching speech sounds and larger units of speech to their written counterparts. GG has been shown to benefit children with reading difficulties and the game is now available for all Finnish school children for literacy support. Presently millions of children in Africa fail to learn to read despite years of primary school education. As many African languages have transparent writing systems similar in structure to Finnish, it was hypothesized that GG-based training of letter-sound correspondences could also be effective in supporting children's learning in African countries. In this article we will describe how GG has been developed from a Finnish dyslexia prevention game to an intervention method that can be used not only to improve children's reading performance but also to raise teachers' and parents' awareness of the development of reading skill and effective reading instruction methods. We will also provide an overview of the GraphoGame activities in Zambia, Kenya, Tanzania, and Namibia, and the potential to promote education for all with a combination of scientific research and mobile learning.